2000
DOI: 10.1093/ajcn/71.1.94
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of iron absorption in men consuming diets with high or low iron bioavailability

Abstract: Background: Short-term measurements of iron absorption are substantially influenced by dietary bioavailability of iron, yet bioavailability negligibly affects serum ferritin in longer, controlled trials. Objective: Our objective was to test the hypothesis that in men fed diets with high or low iron bioavailability, iron absorption adapts to homeostatically maintain body iron stores. Design: Heme-and nonheme-iron absorption from whole diets were measured in 31 healthy men at 0 and 10 wk while the men consumed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
2
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(99 citation statements)
references
References 44 publications
4
88
2
5
Order By: Relevance
“…The lack of significant change in iron indexes by Hunt and Roughead (25) and in our study may be a reflection of an adaptation of nonheme iron absorption, as found in a recent study (27) in which men adapted over time to diets of high and low iron bioavailabilities. This adaptive response was noted by decreased nonheme iron absorption of the men who consumed high bioavailable iron diets and an increased nonheme iron absorption in men who consumed low bioavailable iron diets over time.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The lack of significant change in iron indexes by Hunt and Roughead (25) and in our study may be a reflection of an adaptation of nonheme iron absorption, as found in a recent study (27) in which men adapted over time to diets of high and low iron bioavailabilities. This adaptive response was noted by decreased nonheme iron absorption of the men who consumed high bioavailable iron diets and an increased nonheme iron absorption in men who consumed low bioavailable iron diets over time.…”
Section: Discussionsupporting
confidence: 81%
“…In contrast, iron status indexes did respond to dietary intervention (26) in a seven-week crossover design study in postmenopausal women comparing controlled high meat, low meat, and low meat plus mineral supplement diets, all similar in phytate content. Opposite of what would have been expected, that a high meat diet would increase iron stores and/or positively affect iron status, the high meat diet resulted in decreased ferritin and increased TIBC.The lack of significant change in iron indexes by Hunt and Roughead (25) and in our study may be a reflection of an adaptation of nonheme iron absorption, as found in a recent study (27) in which men adapted over time to diets of high and low iron bioavailabilities. This adaptive response was noted by decreased nonheme iron absorption of the men who consumed high bioavailable iron diets and an increased nonheme iron absorption in men who consumed low bioavailable iron diets over time.…”
supporting
confidence: 55%
“…The association between tea intake and iron status was addressed in two studies (Hunt & Roughead, 2000;Imai & Nakachi, 1995), of which one was an experiment (Hunt & Roughead, 2000; Table 3). The parallel designed experiment (Hunt & Roughead, 2000) in 31 healthy men (age !…”
Section: Menmentioning
confidence: 99%
“…The parallel designed experiment (Hunt & Roughead, 2000) in 31 healthy men (age ! 32 y) showed successful adaptation of iron absorption to diets with low iron bioavailability containing tea (from 1 g dry, black instant) with each meal.…”
Section: Menmentioning
confidence: 99%
“…Vitamin C is known to improve iron absorption by preventing the formation of insoluble iron complexes with tannins and phytates. Vitamin C also converts ferric iron to ferrous form which is the required form for absorption by the intestinal mucosal cells [72].…”
Section: Favorable or Synergistic Nutrient Interactionsmentioning
confidence: 99%